Mercado de capitales, intermediación financiera y crecimiento económico en el Perú: 1998-2008 - Cortez Cortez, Gaby (2010)
In line with theoretical and empirical evidence on the relationship between development of financial intermediaries and capital markets with economic growth, we have found the existence of a positive relationship between the developments of the Peruvian financial system and economic growth during the period 1998- 2008. These results suggest that the development of banks measured by bank credit, support and follow economic growth, and therefore suggests that banks only play a strictly technical function of allocating resources in the production process. On the other hand, empirical evidence shows us that economic growth is not explained by capital market development, concluding that the capital market is not an important source of financial resources for the growth of economic activity in Peru.